Improving Students’ Critical Thinking Ability Through a Project Based Learning Model on Basic Laws of Chemistry Concepts - Jusniar, Jusniar; Syamsidah, Syamsidah; Auliah, Army; Fadly, Dewiyanti (Journal of Ecohumanism, 2025)
This descriptive research aims to provide an overview of critical thinking ability (CTA) through the implementation of the Project-Based Learning model. The description is carried out based on the categorization of the normalized gain results according to Meltzser from the CTA aspect, namely interpretation, analysis, inference, deduction and evaluation abilities. The research subjects were Class XE1 of SMAN 1 Gowa with 35 students. Data collection on critical thinking skills using essay tests for basic laws of chemistry. From the research data, the N Gain Score value for all indicators of critical thinking skills is in the medium category. The N Gain Score value for the critical thinking skills indicator, namely interpretation skills is 74%, analysis skills is 56%, inference skills is 67%, deduction skills is 55%, and evaluation skills is 48. With this increase it can be concluded that the Project-Based Learning model is able to improve skills students’ critical thinking on basic laws of chemistry.